Propose Marketing Strategy PT Mulia Bersinar (The Indonesian Journal of Business Administration, 2015)
Abstract.Agribusiness has been already became one of Indonesian economic buffers. It can be seen on the percentage level of agribusiness composition in Indonesia non-oil and gas GDP. The object of agribusiness can be farms or plantations and livestocks. PT Pelita Mulia Bersinar is a company in livestock business that implementing cooperation concept with all chicken farmers in production area and the B2B sales area. But PT Pelita Mulia Bersinar experienced high revenue fluctuation from time to time. This research aim to propose new marketing strategy and also the implementation with budgeting plan of the proposed marketing strategy for PT Pelita Mulia Bersinar.Keywords: Chicken Farms, Marketing Strategy